Working through frame incongruences : A process perspective on (re)framing for digital servitization - Raja, Jawwad Z.; Neufang, Isabelle Fabienne; Frandsen, Thomas; Gölgeci, Ismail (Elsevier, 2023)
Industrial firms are increasingly seeking new means of competitiveness through digital servitization that involves incorporating digital services and platforms. Despite the growing prominence of digital servitization, we have yet to understand how such changes are being framed, reframed, and unfold in industrial firms. To this end, we undertake an in-depth longitudinal exploratory case study of an industrial firm to understand the organizational framing and reframing activities vis-à-vis digital servitization. Our findings identify how motivational, diagnostic, and prognostic framing gradually unfolds over distinct phases. Specifically, our findings reveal the occurrence of frame incongruence among different groups of actors, compelling the firm to engage in strategies and tactics to achieve frame alignment. Notably, we identify that management engages in the alignment processes of frame extension, translation, and clarification, which creates a space of workable certainty. While transient in nature, this state of workable certainty serves as a catalyst in propelling the firm forward in its pursuit of a digital servitization strategy. By shedding light on the process of digital reframing that firms undertake in order to materialize their digital servitization strategy, our study contributes to a deeper understanding of this phenomenon. Moreover, we raise pertinent managerial implications for firms embarking on the path of digital servitization, emphasizing the imperative of continuous attention to the ongoing framing and reframing processes accompanying such change endeavors.
Keywords: Digitalization; Digital servitization; Frames; Reframing; Alignment